Hotel travel recommendation based on blog information - Zulkefli, N.A.B.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
In this paper, we presenting our proposed recommending hotels for the users based on the userexperience reviews in blog. Usually, hotel recommendation systems recommend hotels based on non-spatial attributes of hotels such as price and rating and do not utilize surrounding environments well. In contrast, we consider the existing of much information in blogs that have a substantial input of surrounding conditions. The information in the blog is useful as user review the hotel based on their experience and some information contains many pictures and video that can improve the hotel travel recommendation results. In this work the hotel recommendation provides the suggested hotel by learning the user's preferences. Each user's preference is used as a key t o f ind t he i nformation i n blogs. M eanwhile, t he ranking result for all blogs is filtered by users who rate each blog, in terms of whether or not they can find hotel information. Finally, results will be displayed based on the blog ranking. Â© 2015 IEEE.